Produced water's impact on soil properties: Remediation challenges and opportunities - A. Green; T.M. DeSutter; M.A. Meehan; A.L.M. Daigh; P.L. O'Brien (Agrosystems, Geosciences & Environment, 2020)
Abstract The choice of remediation of oil‐produced water (aka brine) spills depends on the severity of contamination, environmental factors, cost‐effectiveness, and relative efficiency of salt removal. The objective of this review is to summarize the current practices that are used to remediate brine spills or abandoned evaporation pits within the Bakken and Three Forks regions of the Williston Basin within the upper Great Plains. The most common current methods are “dig and haul” and the use of chemical amendments such as gypsum (CaSO4) or organic amendments (manure, straw, etc.) to promote soil flocculation and the downward leaching of salts out of the topsoil. These methods, however, can fail to achieve sustained remediation success in a cost‐effective and timely manner, making continued research into alternative methods necessary. The use of electrokinetics, crystallization inhibitors, wicking materials, and plant‐growth promoting rhizobacteria hold promise for in‐situ cleanup of contaminated sites.